094 Vascular targeting of phosphatidylserine causing thrombotic occlusion in an arteriovenous malformation animal model. Issue 6 (24th May 2018) - Stoodley, Marcus; Gauden, Andrew; Lee, Vivienne; Subramanian, Sinduja; Moutrie, Vaughan; Zhao, Zhenjun; McRobb, Lucinda
Abstract : Introduction: One third of brain arteriovenous malformations (AVMs) are untreatable with current methods. Previous work has identified phosphatidylserine externalised in the endothelial plasma membrane after treatment with radiosurgery as a potential target for biological pro-thrombotic therapy. We hypothesise that treatment of AVMs with Gamma knife radiosurgery (GKS) and a vascular targeting agent with a thrombotic compound will cause localised thrombosis within the AVM vessels. Methods: A rat animal model was used by performing an end-to-side anastomosis of the external jugular vein (EJV) to the common carotid artery. The model AVM was treated with radiosurgery (20 Gy) using a Leksell Gamma Knife. At 3 weeks following GKS a dose of a conjugate of annexin V and thrombin was administered intravenously. Groups injected with saline or thrombin alone were used as controls. At 4 weeks, an angiogram was performed with tissue harvested for histology. Results: There was angiographic evidence of AVM occlusion in 69% of conjugate-treated animals and none of the control animals (p=0.002). AVM occlusion occurred in 63% of the GKS group treated with conjugate (p=0.03), and in 75% of the sham-GKS conjugate treated group (p=0.009). Histological evidence of thrombus was present within the EJV and nidus of 62.5% of animals in the GKS with conjugate group and <25% of the control groups (p=0.026). Conclusion: This study demonstrates that targeting of PS with an annexin V-thrombin conjugate is effective in causing thrombotic occlusion in a model AVM. These results are the first of their kind and indicate that ligand vascular targeting with radiation sensitisation may become a potential future treatment in brain AVMs.